2006
DOI: 10.1111/j.1462-2920.2006.01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and mechanism of filamentous‐sulfur formation by Candidatus Arcobacter sulfidicus in opposing oxygen‐sulfide gradients

Abstract: Studies were conducted in opposing gradients of oxygen and sulfide in microslide capillaries to (i) characterize the chemical microenvironment preferred by Candidatus Arcobacter sulfidicus, a highly motile, sulfur-oxidizing bacterium that produces sulfur in filamentous form, and (ii) to develop a model describing the mechanism of filamentous-sulfur formation. The highly motile microorganisms are microaerophilic, with swarms effectively aggregating within oxic-anoxic interfaces by exhibiting a chemotactic respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 21 publications
7
103
1
1
Order By: Relevance
“…These bacteria, like the chemolithoautotroph Candidatus A. sulfidicusrelated OTU (Otu7), would prefer to fix the inorganic carbon present in seawater. Arcobacter-related OTUs may be responsible for the white coloration observed on our mat because they do an incomplete oxidation of sulfide to elemental sulfur, which produces white sulfur filaments visible to the naked eye (Wirsen et al, 2002;Sievert et al, 2007). In addition to the visual observation of this elemental sulfur, we detected Deferribacteres OTUs that might utilize this Figure 6 Schematic illustration of the ecological succession within the epixylic mat.…”
Section: Ecological Succession During Epixylic Mat Formationmentioning
confidence: 92%
See 2 more Smart Citations
“…These bacteria, like the chemolithoautotroph Candidatus A. sulfidicusrelated OTU (Otu7), would prefer to fix the inorganic carbon present in seawater. Arcobacter-related OTUs may be responsible for the white coloration observed on our mat because they do an incomplete oxidation of sulfide to elemental sulfur, which produces white sulfur filaments visible to the naked eye (Wirsen et al, 2002;Sievert et al, 2007). In addition to the visual observation of this elemental sulfur, we detected Deferribacteres OTUs that might utilize this Figure 6 Schematic illustration of the ecological succession within the epixylic mat.…”
Section: Ecological Succession During Epixylic Mat Formationmentioning
confidence: 92%
“…This genera of sulfatereducing bacteria is strictly anaerobic, uses fermentation end products as a carbon source, respires sulfate and thus produces hydrogen sulfide (Pradel et al, 2013). The mat thickness increase with time may be linked to the displacement of the oxygensulfide interface from the wood surface toward the seawater as observed on other Epsilonproteobacteria mats (Wirsen et al, 2002;Sievert et al, 2007). This displacement limits the penetration of potential electron acceptors like oxygen and nitrate, thus promoting the development of anaerobic and nitrate depleted niches (Van Houten et al, 1994;Okabe et al, 2005) on the wood side of the mat as shown by the microsensor measurements taken in our second experiment (Figure 5c).…”
Section: Ecological Succession During Epixylic Mat Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of flexibility in regard to oxygen not only defines the ecological niches of specific organisms but largely affects cultivation success (202). Recently, several microaerophilic organisms that thrive strictly at the oxic-anoxic interface and tolerate oxygen only at specific and low concentrations have been isolated (55,153,193,216). To maximize the cultivation success, the simulation of the natural environmental conditions is critical, and the degree of specificity increases with the specificity of the requirements and tolerances of the organism.…”
Section: Why Are Most Bacteria Currentlymentioning
confidence: 99%
“…For example, in all incubations, the amount of nitrate and oxygen consumed was never sufficient to account for the complete oxidation of sulfide to sulfate (supplemental spreadsheet), suggesting that sulfide was oxidized to an intermediate oxidation state sulfur species. Some autotrophic Epsilonproteobacteria can catalyze sulfide oxidation to elemental sulfur (S 0 ) (Wirsen et al, 2002;Sievert et al, 2007), and indeed white flocculent material (likely composed of S 0 ) continuously emanates from Crab Spa.…”
Section: Biogeochemistry Of Sulfur and Nitrogenmentioning
confidence: 99%